2014
DOI: 10.3895/s1981-36862014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Polpa De Camu-Camu Liofilizada E Armazenada Em Diferentes Embalagens

Abstract: O camu-camu, fruto Amazônico, possui altos teores de ácido ascórbico além de outros importantes componentes com atividade antioxidante, a utilização desses recursos naturais pode resultar em maior desenvolvimento da região de sua origem. No Brasil, sua comercialização é limitada a frutas frescas, mas muitas pesquisas procuram produtos transformados que podem ser facilmente transportados e armazenados. O objetivo deste estudo foi avaliar a qualidade físico-química de polpa de camu-camu desidratada por liofiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
2
6
0
1
Order By: Relevance
“…At the end of the storage, all powders, despite the significant reductions of luminosity (L*), were classified as clear, with values higher than 70. A behavior similar to that observed in the pulp powders of the present study were reported by Liu et al (2010) and Juliano et al (2014) in pulps of tomato and 'camu-camu' along 5 months and 150 days of storage, respectively, with significant reduction of L* during the evaluated period.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…At the end of the storage, all powders, despite the significant reductions of luminosity (L*), were classified as clear, with values higher than 70. A behavior similar to that observed in the pulp powders of the present study were reported by Liu et al (2010) and Juliano et al (2014) in pulps of tomato and 'camu-camu' along 5 months and 150 days of storage, respectively, with significant reduction of L* during the evaluated period.…”
Section: Resultssupporting
confidence: 90%
“…The water content tended to increase over the storage period, indicating that the utilized package allowed water diffusion from the environment to the studied powders. This phenomenon is in agreement with Juliano et al (2014), who reported reduction of water content in 'camu-camu' pulp powder along 150 days of storage at 25 ºC.…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations